Intercontinental dissemination of azithromycin-resistant shigellosis through sexual transmission: a cross-sectional study. Issue 8 (August 2015) - Baker, Kate S; Dallman, Timothy J; Ashton, Philip M; Day, Martin; Hughes, Gwenda; Crook, Paul D; Gilbart, Victoria L; Zittermann, Sandra; Allen, Vanessa G; Howden, Benjamin P; Tomita, Takehiro; Valcanis, Mary; et al.
Summary: Background: Shigellosis is an acute, severe bacterial colitis that, in high-income countries, is typically associated with travel to high-risk regions (Africa, Asia, and Latin America). Since the 1970s, shigellosis has also been reported as a sexually transmitted infection in men who have sex with men (MSM), in whom transmission is an important component of shigellosis epidemiology in high-income nations. We aimed to use sophisticated subtyping and international sampling to determine factors driving shigellosis emergence in MSM linked to an outbreak in the UK. Methods: We did a large-scale, cross-sectional genomic epidemiological study of shigellosis cases collected from 29 countries between December, 1995, and June 8, 2014. Focusing on an ongoing epidemic in the UK, we collected and whole-genome sequenced clinical isolates of Shigella flexneri serotype 3a from high-risk and low-risk regions, including cases associated with travel and sex between men. We examined relationships between geographical, demographic, and clinical patient data with the isolate antimicrobial susceptibility, genetic data, and inferred evolutionary relationships. Findings: We obtained 331 clinical isolates of S flexneri serotype 3a, including 275 from low-risk regions (44 from individuals who travelled to high-risk regions), 52 from high-risk regions, and four outgroup samples (ie, closely related, but genetically distinct isolates used to determine the root of the phylogenetic tree). We identified a recently emerged lineage of S flexneri 3a that has spread intercontinentally in less than 20 years throughout regions traditionally at low risk for shigellosis via sexual transmission in MSM. The lineage had acquired multiple antimicrobial resistance determinants, and prevailing sublineages were strongly associated with resistance to the macrolide azithromycin. Eight (4%) of 206 isolates from the MSM-associated lineage were obtained from patients who had previously provided an isolate; these serial isolations indicated atypical infection patterns (eg, reinfection). Interpretation: We identified transmission-facilitating behaviours and atypical course(s) of infection as precipitating factors in shigellosis-affected MSM. The intercontinental spread of antimicrobial-resistant shigella through established transmission routes emphasises the need for new approaches to tackle the public health challenge of sexually transmitted infections in MSM. Funding: Wellcome Trust (grant number 098051).